2020
DOI: 10.1042/bsr20202376
|View full text |Cite
|
Sign up to set email alerts
|

A six-gene-based signature for breast cancer radiotherapy sensitivity estimation

Abstract: Breast cancer (BRCA) represents the most common malignancy among women worldwide with high mortality. Radiotherapy is a prevalent therapeutic for BRCA that with heterogeneous effectiveness among patients. Here, we proposed to develop a gene expression-based signature for BRCA radiotherapy sensitivity estimation. Gene expression profiles of BRCA samples from the Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) were obtained and used as training and independent testing dataset, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…While a clear step forward, RRS remains a prognostic signature for loco-regional control, and not predictive of radiation response. Similar predictive gene signatures have been developed, including a six-gene signature (including genes such as HOXB13 and NKX2-2) that was also shown to predict radiotherapy sensitivity in breast cancer [ 77 ]. Applying a 24-gene signature to prostate cancer patients who had undergone radical prostatectomy to identify those most likely to benefit from postoperative radiotherapy similarly found that those with a high PROTOS (postoperative radiation therapy outcomes score), indicative of radiation-sensitive tumours, significantly benefited from radiotherapy, with a 10-year metastasis rate of 4% (95% CI 0–10) versus 35% (CI 7–54) for those not receiving radiotherapy.…”
Section: Predictive Biomarkers Of Radiation Responsementioning
confidence: 99%
“…While a clear step forward, RRS remains a prognostic signature for loco-regional control, and not predictive of radiation response. Similar predictive gene signatures have been developed, including a six-gene signature (including genes such as HOXB13 and NKX2-2) that was also shown to predict radiotherapy sensitivity in breast cancer [ 77 ]. Applying a 24-gene signature to prostate cancer patients who had undergone radical prostatectomy to identify those most likely to benefit from postoperative radiotherapy similarly found that those with a high PROTOS (postoperative radiation therapy outcomes score), indicative of radiation-sensitive tumours, significantly benefited from radiotherapy, with a 10-year metastasis rate of 4% (95% CI 0–10) versus 35% (CI 7–54) for those not receiving radiotherapy.…”
Section: Predictive Biomarkers Of Radiation Responsementioning
confidence: 99%
“…Some patients are more sensitive to radiotherapy while others may not benefit from the radiotherapy. Recently, Chen et al [ 1 ] developed a signature for breast cancer radiosensitivity and this signature shed new light in the treatment of breast cancer.…”
mentioning
confidence: 99%
“…Recently, a six-gene-based signature established a prediction model for breast cancer radiotherapy sensitivity estimation [ 1 ]. The six genes in this signature include HOXB13, NKX2-2, ADAMTS20 , LOC284930, ACTL8 and LOC101928978 [ 1 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations